Method of levels therapy for first-episode psychosis: rationale, design and baseline data for the feasibility randomised controlled Next Level study. Issue 5 (14th August 2018) - Griffiths, Robert; Mansell, Warren; Carey, Timothy A.; Edge, Dawn; Emsley, Richard; Tai, Sara J.
Abstract : Background: Method of levels (MOL) is an innovative transdiagnostic cognitive therapy with potential advantages over existing psychological treatments for psychosis. Aims: The Next Level study is a feasibility randomised controlled trial (RCT) of MOL for people experiencing first-episode psychosis. It aims to determine the suitability of MOL for further testing in a definitive trial (trial registration ISRCTN13359355). Method: The study uses a parallel group non-masked feasibilityRCT design with two conditions: (a) treatment as usual (TAU) and (b) TAU plus MOL. Participants ( n = 36) were recruited from early intervention in psychosis services. Outcome measures are completed at baseline, 10 and 14 months. The primary outcomes are recruitment and retention. Results: Participants' demographic and clinical characteristics are presented along with baseline data. Conclusions: Next Level has recruited to target, providing evidence that it is feasible to recruit to a RCT of MOL for first-episode psychosis. Declaration of interest: None.